Somerset appendix details table - Thorn, Frank; Thorn, Caroline (The University of Hull)
The first appendix (Somerset Appendix 1a) analyses the two Bath 'satellite' texts (Bath A and B) and the additional or variant material they supply, plus assessments and ploughteams recorded in the "Liber Exoniensis" (Exon) but omitted from Domesday Book; the second appendix (Somerset Appendix Details Table 1a) supplies details of the subholdings omitted from Domesday Book. These appendices are taken from the Phillimore printed edition (1980) edited by Caroline and Frank Thorn and have been lightly revised by Caroline and Frank Thorn.